Investigation of Vitamins, Glutathione and Stress Biomarkers in Blood Serum of Patients with Breast Cancer - Dursun Özer; Sinan Saydam; Awat Hamad Awla Ibraım; Fikret Karataş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Breast cancer is a genetic disease caused by the accumulation of mutations in neoplastic cells and is responsible for the highest morbidity and mortality. In this study, blood serum samples from 45 breast cancer patients and 32 healthy individuals (control group) were used. The amounts of vitamins (A, E, β-carotene, C, B1, B2, B3, B5, B6, B9 and B12), glutathione (GSH, GSSG) stress biomarkers (4-HNE, MDA) were determined by HPLC. A significant difference was found between the breast cancer patients and the control group in terms of age and body mass index (BMI) (p